2016
DOI: 10.1002/ijc.30447
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of heritability for nine common cancers using data from genome‐wide association studies in Chinese population

Abstract: The familial aggregation indicated the inheritance of cancer risk. Recent genome-wide association studies (GWAS) have identified a number of common single nucleotide polymorphisms (SNPs). Following heritability analyses have shown that SNPs could explain a moderate amount of variance for different cancer phenotypes among Caucasians. However, little information was available in Chinese population. We performed a genome-wide complex trait analysis (GCTA) for common cancers at nine anatomical sites in Chinese pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 49 publications
(94 reference statements)
1
87
0
Order By: Relevance
“…Roughly 15% to 20% of CRC diagnoses occur in individuals who have at least one first‐degree relative with the disease, and such families are often labeled as having “familial CRC.” Despite this label, however, it has generally been recognized that fewer than 5% of patients with CRC harbor germline variants in CRC susceptibility genes, indicating that the majority of such familial CRC heritability remains unexplained by identifiable monogenic germline variants. Although as‐yet‐unidentified CRC susceptibility genes may explain some of this missing heritability, polygenic, environmental, and/or behavioral factors may account for much of this unexplained risk …”
Section: Germline Basis Of Familial Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…Roughly 15% to 20% of CRC diagnoses occur in individuals who have at least one first‐degree relative with the disease, and such families are often labeled as having “familial CRC.” Despite this label, however, it has generally been recognized that fewer than 5% of patients with CRC harbor germline variants in CRC susceptibility genes, indicating that the majority of such familial CRC heritability remains unexplained by identifiable monogenic germline variants. Although as‐yet‐unidentified CRC susceptibility genes may explain some of this missing heritability, polygenic, environmental, and/or behavioral factors may account for much of this unexplained risk …”
Section: Germline Basis Of Familial Crcmentioning
confidence: 99%
“…Although as-yet-unidentified CRC susceptibility genes may explain some of this missing heritability, polygenic, environmental, and/or behavioral factors may account for much of this unexplained risk. [15][16][17][18] The commonest form of familial CRC in which specific germline variants can be identified is Lynch syndrome, which is associated with alterations in 4 DNA MMR genes-mutS homolog 2 (MSH2) plus epithelial cell adhesion molecule (EpCAM), mutL homolog 1 (MLH1), mutS homolog 6 (MSH6), and PMS1 homolog 2 (PMS2). This entity is recognized by the near-universal presence of MSI in the tumors.…”
Section: Germline Basis Of Familial Crcmentioning
confidence: 99%
“…In the past decade, genome‐wide association studies (GWAS) successfully identified lots of lung cancer susceptibility loci, such as CHRNA5 ‐ CHRNA3 ‐ CHRNB4 region of chromosome 15q25 and human leukocyte antigen region. Even so, at least 25% of lung cancer cases were never smokers and the heritability of lung cancer was also relatively low, nearly 18% . The risk factors of lung cancer still need more exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Although tobacco smoking is a major lung cancer risk factor, genetic factors also play an important role in lung carcinogenesis. According to previous studies, common SNPs can explain approximately 12–21% heritability in lung cancer in Asian and European populations . Genome‐wide association studies (GWAS) have previously identified 45 susceptibility loci associated with lung cancer, and single nucleotide polymorphisms (SNPs) in the CHRNA3 , CHRNA5 , TERT and human leukocyte antigen (HLA) regions showed consistent and robust associations in different studies.…”
Section: Introductionmentioning
confidence: 99%